Interactive road map system kiosk: the readiness among Malaysian society / Mohamad Rasid Ruhani - Ruhani, Mohamad Rasid (2006)
Most of the Malaysian mainly motorist, faces a difficulties to find a location with a road system in Malaysia. The same problem faced is not only in Malaysia, people the entire world still not comfortable with a conventional map system and always ended with frustrating in using it.